Pengaruh Kepuasan Pelanggan dan Switching Barrier terhadap Loyalitas Pelanggan Pengguna Kartu Prabayar Mentari di Wilayah Semarang Selatan - Dwi Lestari; Suhaji Suhaji (STIE Widya Manggala, 2012)
The purpose of this research is to know the influence of customer satisfaction and switching barrier on castamer loyality at PT Indosat Tbk. Population in this research are all customer of pre - paid card of Mentari in South Semarang Region, and the sample are 96 customers. The analysis instrument used multiple linier regression. The result of the research shows that there is positive significant influence of customer satisfaction and switching barrier on customer loyalit. Simultaneously, all of the variables, customer value and switching barrier affect customer loyality at PT Indosat Tbk.